A Novel Exophiala Species Associated With Disseminated Granulomatous Inflammation in a Captive Eastern Hellbender (Cryptobranchus alleganiensis alleganiensis) - Hopf, Cynthia; Graham, Erin A.; Gibas, Connie F. C.; Sanders, Carmita; Mele, James; Fan, Hongxin; Garner, Michael M.; Wiederhold, Nathan P.; Ossiboff, Robert; Abou-Madi, Noha (Frontiers in Veterinary Science, 2020)
The genus Exophiala is composed of ubiquitous, pigmented, saprotrophic fungi and includes both terrestrial and waterborne species. Though Exophiala species are generally considered opportunistic pathogens, exophialosis can be an important cause of morbidity and mortality in aquatic and semi-aquatic species. Over a 6-year period, a captive 32-year-old male eastern hellbender (Cryptobranchus alleganiensis alleganiensis), was treated for recurring, slow growing, ventral midline cutaneous masses. Excisional biopsies were characterized histologically by granulomatous dermatitis with low numbers of intralesional, pigmented fungal conidia and hyphae. Bacterial and fungal cultures of the masses and skin were negative on two separate submissions. Polymerase chain reaction amplification of a short fragment of the fungal 28S large subunit (LSU) ribosomal RNA was positive with 100% nucleotide sequence identity to several species of Exophiala. Following recurrence after successive rounds of antifungal therapy, euthanasia was elected. At necropsy, similar dermal granulomatous inflammation and intralesional pigmented fungal elements as observed in excisional biopsies formed a thick band in the dermis and extended through the coelomic body wall. Visceral dissemination was noted in the lung and kidney. Postmortem DNA sequence analysis of a large portion of the fungal LSU as well as the internal transcribed spacer (ITS) from a portion of frozen affected dermis identified the fungus as a novel species, Exophiala sp. 1 (UTHSCSA R-5437).